An evaluation on the epic story of O?uz Kagan by view of heroism myth - Özcan, Tarik (Milli Folklor Dergisi, 2003)
Mythos which were far from religious life itself in the course of time in a community life took especially the world of legends as a shelter. These mythologic symbols are the reflection of archaictypes called human's common mind and these heroism mythos are also one of them. In this study, we will try to show the development trend of heroism mythos in Oguz Kagan legend.
O?uz Ka?an destaninin kahramanlik mi?tosu bakimindan çözümlenmesi?
Keywords: Archaictype; Legend of O?uz Kagan; Mythology